Response of phytoplankton composition to environmental stressors under humidification in three alpine lakes on the Qinghai-Tibet Plateau, China - Gu, Peiwen; Jia, Junmei; Qi, Delin; Gao, Qiang; Zhang, Cunfang; Yang, Xi; Nie, Miaomiao; Liu, Dan; Luo, Yule (Frontiers in Microbiology, 2024)
Owning to their extreme environmental conditions, lakes on the Qinghai-Tibet Plateau have typically displayed a simplistic food web structure, rendering them more vulnerable to climate change compared to lakes in plains. Phytoplankton, undergoing a changing aquatic environment, play a crucial role in the material cycle and energy flow of the food chain, particularly important for the unique fish species of the Tibetan Plateau. To identify the changing environment indexes and determine the the response of phytoplankton composition to the environment change in alpine lakes, three lakes-Lake Qinghai, Lake Keluke and Lake Tuosu-were selected as study areas. Seasonal sampling surveys were conducted in spring and summer annually from 2018 to 2020. Our findings revealed there were significant changes in physicochemical parameters and phytoplankton in the three lakes. Bacillariophyta was the predominant phytoplankton in Lake Qinghai from 2018 to 2020, with the genera Synedra sp., Navicula sp., Cymbella sp. and Achnanthidium sp. predominated altertively. Lake Keluke alternated between being dominated by Bacillariophyta and cyanobacteria during the same period. Dolichospermum sp., a cyanobacteria, was prevalent in the summer of 2018 and 2019 and in the spring of 2020. In Lake Tuosu, Bacillariophyta was the predominant phytoplankton from 2018 to 2020, except in the summer of 2019, which was dominated by cyanobacteria. Synedra sp., Oscillatoria sp., Pseudoanabaena sp., Chromulina sp. and Achnanthidium sp. appeared successively as the dominant genera. Analysis revealed that all three lakes exhibited higher phytoplankton abundance in 2018 that in 2019 and 2020. Concurrently, they experienced higher average temperatures in 2018 than in the subsequent years. The cyanobacteria, Bacillariophyta, Chlorophyta and overall phytoplankton increased with temperature and decreased with salinity and NH4-N. Besides, the ratios of cyanobacteria, and the ratios of Bacillariophyta accounted in total phytoplankton increased with temperature. These findings suggest that cyanobacteria and phytoplankton abundance, especailly Bacillariophyta, may have an increase tendency in the three alpine lakes under warm and wet climate.